2022
DOI: 10.1038/s41378-022-00425-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nanoparticles in liquid with attogram resolution using a microfabricated glass suspended microchannel resonator

Abstract: The use of nanoparticles has been growing in various industrial fields, and concerns about their effects on health and the environment have been increasing. Hence, characterization techniques for nanoparticles are essential. Here, we present a silicon dioxide microfabricated suspended microchannel resonator (SMR) to measure the mass and concentration of nanoparticles in a liquid as they flow. We measured the mass detection limits of the device using laser Doppler vibrometry. This limit reached a minimum of 377… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…M ICROELECTROMECHANICAL systems (MEMSs) have attracted great attention in the field of physical and chemical sensors [1], [2]. In addition, suspended microchannel resonators (SMRs) have been developed for sensing biomaterials because their resonance frequency is highly sensitive, thereby enabling the detection of nano/microscale materials [3], [4], [5]. Burg et al have reported an SMR with resonance frequency of 426.8 kHz, mass resolution of 2.7 × 10 −20 kg in 1 kHz bandwidth, and a quality factor of approximately 9000, where the device was surrounded by a vacuum and filled with nitrogen gas [6].…”
Section: Introductionmentioning
confidence: 99%
“…M ICROELECTROMECHANICAL systems (MEMSs) have attracted great attention in the field of physical and chemical sensors [1], [2]. In addition, suspended microchannel resonators (SMRs) have been developed for sensing biomaterials because their resonance frequency is highly sensitive, thereby enabling the detection of nano/microscale materials [3], [4], [5]. Burg et al have reported an SMR with resonance frequency of 426.8 kHz, mass resolution of 2.7 × 10 −20 kg in 1 kHz bandwidth, and a quality factor of approximately 9000, where the device was surrounded by a vacuum and filled with nitrogen gas [6].…”
Section: Introductionmentioning
confidence: 99%